2018
DOI: 10.1044/2018_jslhr-l-16-0330
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Semantic Feature Analysis Therapy Studies for Aphasia

Abstract: SFA leads to positive outcomes despite the variability of treatment procedures, dosage, duration, and variations to the traditional SFA protocol. Further research is warranted to examine the efficacy of SFA and generalization effects in larger controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 98 publications
0
40
1
2
Order By: Relevance
“…The inclusion of people with severe aphasia should be noted. Unlike the current study, the majority of participants (33/55) in a recent systematic review of SFA studies were fluent and had mostly mild aphasias (Conduction and Anomic), and only 5/55 participants had severe aphasia (Efstratiadou et al, 2018). In contrast, in our study 19/38 (50%) of participants had severe aphasia.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The inclusion of people with severe aphasia should be noted. Unlike the current study, the majority of participants (33/55) in a recent systematic review of SFA studies were fluent and had mostly mild aphasias (Conduction and Anomic), and only 5/55 participants had severe aphasia (Efstratiadou et al, 2018). In contrast, in our study 19/38 (50%) of participants had severe aphasia.…”
Section: Discussioncontrasting
confidence: 88%
“…This is an important finding that adds to current knowledge on maintenance of gains after SFA. In a recent systematic review of SFA studies (Efstratiadou et al, 2018), maintenance was reported for 58.18% of participants, but most of the included studies assessed maintenance in the short term, with only 2/21 studies assessing maintenance at 3 months or longer post therapy and only 1/4 participants in these two studies showing a positive effect (Davis & Stanton, 2005;Kristensson, Behrns & Saldert, 2015). Lastly, significant others perceived an improvement on participants' functional communicational skills at the follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as the qualitative reviews discussed above, three systematic reviews of verb treatments have been conducted since 2013 (Efstratiadou, Papathanasiou, Holland, Archonti, & Hilari, 2018;Maddy, Capilouto & McComas, 2014;Rose, Raymer, Lanyon & Attard, 2013) and all of these contribute to our understanding of the effectiveness of verb treatments. However, none of these encompassed all researched treatments for verbs or included an evaluation of treatment fidelity.…”
Section: Existing Reviews Of Verb Treatmentsmentioning
confidence: 99%
“…However, none of these encompassed all researched treatments for verbs or included an evaluation of treatment fidelity. Maddy et al (2014) and Efstratiadou et al (2018) both conducted systematic reviews restricted to Semantic Feature Analysis (SFA) treatment, including studies that used SFA to treat nouns or discourse, as well as those which targeted verbs. The methodological quality of the reviewed studies was evaluated using the Single Case Experimental Design (SCED) Scale (Tate et al, 2008) and effect sizes were calculated (using Cohen's d and benchmarks specified by Beeson and Robey (2006)) to evaluate the effectiveness of SFA.…”
Section: Existing Reviews Of Verb Treatmentsmentioning
confidence: 99%